PENGARUH PEMBERIAN NAUNGAN DAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN STROBERI (Fragaria sp.) DI DATARAN RENDAH - Choerul Bahri; Ardian Ardian; Syafrinal Syafrinal (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The use of strawberry cultivation land is limited in the highlands, it is necessary to develop the adaptation of strawberry plants to lowland cultivation areas, especially in Riau. The research was purpose to study the effect of shade and liquid organic fertilizer concentration on growth and yield of strawberries in lowland. The research was conducted using a Split Plot Design, with the shading as main plots (shade 0%, 50% and 75%) and giving liquid organic fertilizer concentration as subplots (0 ml/l, 2,5 ml/l, 5 ml/l dan 7,5 ml/l). Observed variable is the number of plant height and leaf, flowering age, number of flowers, number of fruits, total fruits weight. The data were analyzed by anova and descriptive analyse, than followed by Duncan’s multiple range test at 5% level. The result of this study represent that was significant different of shade on the number of plant heigh and leaf, but its no complete data on the flowering age, number of flowers, number of fruits, total fruits weight. The best treatment for growth of strawberries is shade as 50% and liquid organic fertilizer concentration as 7,5 ml/l of water.Keywords: strawberry, adaptation, shade, liquid organic fertilizer